Direct laser additive manufacturing of high performance oxide ceramics: A state-of-the-art review. Issue 13 (October 2021) - Pfeiffer, Stefan; Florio, Kevin; Puccio, Dario; Grasso, Marco; Colosimo, Bianca Maria; Aneziris, Christos G.; Wegener, Konrad; Graule, Thomas
Highlights: Laser Additive Manufacturing processes for ceramics are critically analyzed. The state of the art for powder preparation and processing is described in detail. Advantages compared to other Additive Manufacturing processes are summarized. Part properties, open challenges and potential developments are discussed. The state of the art for process monitoring and its potential are highlighted. Abstract: The implementation of additive manufacturing for ceramics is more challenging than for other material classes, since most of the shaping methods require polymer binder. Laser additive manufacturing (LAM) could offer a new binder-free consolidation route, since it is capable of processing ceramics in a direct manner without post-processing. However, laser processing of ceramics, especially high performance oxide ceramics, is limited by low thermal shock resistance, weak densification and low light absorptance at room temperature; particularly in the visible or near-infrared range. An extensive review focusing only on LAM (powder bed fusion – laser beam and directed energy deposition) of high performance oxide ceramics is currently lacking. This state-of-the-art review gives a detailed summary and critical analysis about process technologies, part properties, open challenges and process monitoring in the field of oxide ceramics. Improvements in accuracy and mechanical strength are proposed that could open LAM of oxide ceramics to new fields.